Landslide mechanism and stability of an open-pit slope: The Manglai open-pit coal mine - Chen, Tao; Shu, Jisen; Han, Liu; Tovele, Gerson. S. V.; Li, Baosheng (Frontiers in Earth Science, 2023)
A clear understanding of landslide mechanisms and stability analyses is of great significance for landslide monitoring, prediction, and control. A large-scale end wall landslide occurred on August 7–20, 2020, in the Manglai open-pit coal mine, China. In this paper, the engineering geological survey, mechanical test, large-deformation finite element numerical method, limit equilibrium method and analytical formula are used to analyze how the groundwater level rise caused this end wall failure and landslide. First, the engineering geological conditions, hydrogeological conditions, landslide activity signs and physical and mechanical parameter calibration of the sliding mass are investigated in detail and tested, mainly including the rock distribution, lithologic characteristics, structure, fault, cumulative rainfall, groundwater level burial depth, water inflow, landslide process and testing of mechanical parameters such as cohesion and internal friction angle of the sliding mass. Second, three-dimensional and two-dimensional numerical models of slopes are established, and an analytical formula calculation method to calculate the factor of safety (FoS) is proposed when sliding cracks are located on the top and toe of a slope. Finally, the causes of the landslide, mechanism and stability are analyzed and discussed. The results indicate that the fault fracture zone, soft strata, continuous heavy rainfall, and groundwater were the main contributors to this landslide. The three-dimensional numerical calculation results are consistent with the deformation and failure process of the slope observed in the field, which shows a retrogressive progressive failure mode. The calculation results of SLOPE/W and the analytical formula are consistent; i.e., when the groundwater level rises to +950, the stability of the end wall reaches the critical stability state. With the passage of time, the creep of the sliding surface accelerates until the entire end wall landslide.